Electrical steels. - Moses, Anthony (Professor of Magnetics); Jenkins, Keith (Electrical steels researcher); Anderson, Philip (Senior Lecturer); Stanbury, Hugh (IET energy engineering series ;, 2019)
Electrical steels are critical components of magnetic cores used in applications ranging from large rotating machines, including energy generating equipment, and transformers to small instrument transformers and harmonic filters. This comprehensive handbook provides full coverage of the state-of-the-art in electrical steels.